Experimental evidence for splicing of intron-containing transcripts of plant LTR retrotransposon Ogre - Steinbauerová, Veronika; Neumann, Pavel; Macas, Jirí (Molecular genetics and genomics, 2008)
Ogre elements are a distinct group of plant Ty3/gypsy-like retrotransposons characterized by several specific features, one of which is a separation of the gag-pol region into two non-overlapping open reading frames: ORF2 coding for Gag-Pro, and ORF3 coding for RT/RH-INT proteins. Previous characterization of Ogre elements from several plant species revealed that part of their transcripts lacks the region between ORF2 and ORF3, carrying one uninterrupted ORF instead. In this work, we investigated a hypothesis that this region represents an intron that is spliced out from part of the Ogre transcripts as a means for preferential production of ORF2-encoded proteins over those encoded by the complete ORF2-ORF3 region. The experiments involved analysis of transcription patterns of well-defined Ogre populations in a model plant Medicago truncatula and examination of transcripts carrying dissected pea Ogre intron expressed within a coding sequence of chimeric reporter gene. Both experimental approaches proved that the region between ORF2 and ORF3 is spliced from Ogre transcripts and showed that this process is only partial, probably due to weak splice signals. This is one of very few known cases of spliced LTR retrotransposons and the only one where splicing does not involve parts of the element's coding sequences, thus resembling intron splicing found in most cellular genes.
Keywords: semena rostlinná; sekvence nukleotidů; Genome, Plant; genom rostlinný; Transcription, Genetic; molekulární sekvence - údaje; retroelementy; Seeds; Retroelements; Introns; DNA rostlinná; genetická transkripce; Pisum sativum; DNA, Plant; Medicago truncatula; introny; alternativní sestřih; otevřené čtecí rámce; Open Reading Frames; hrách setý; Molecular Sequence Data; Alternative Splicing; Base Sequence; Terminal Repeat Sequences; koncové repetice